2014
DOI: 10.1214/14-aoas764
|View full text |Cite
|
Sign up to set email alerts
|

A novel spectral method for inferring general diploid selection from time series genetic data

Abstract: The increased availability of time series genetic variation data from experimental evolution studies and ancient DNA samples has created new opportunities to identify genomic regions under selective pressure and to estimate their associated fitness parameters. However, it is a challenging problem to compute the likelihood of non-neutral models for the population allele frequency dynamics, given the observed temporal DNA data. Here, we develop a novel spectral algorithm to analytically and efficiently integrate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
179
5

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(185 citation statements)
references
References 24 publications
1
179
5
Order By: Relevance
“…In contrast, the ASIP locus is inferred to be overdominant under a constant-size demography, but the complicated demographic history results in an inference of positive selection and a much older allele age. These results stand in contrast to those of Steinrücken et al (2014), who found that the most likely mode of evolution for both loci under a constant demographic history is one of overdominance. There are a several reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast, the ASIP locus is inferred to be overdominant under a constant-size demography, but the complicated demographic history results in an inference of positive selection and a much older allele age. These results stand in contrast to those of Steinrücken et al (2014), who found that the most likely mode of evolution for both loci under a constant demographic history is one of overdominance. There are a several reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…These results stand in contrast to those of Steinrücken et al (2014), who found that the most likely mode of evolution for both loci under a constant demographic history is one of overdominance. There are a several reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The many areas where this design has been applied include demographic inference (see [1] for a recent review), recombination rate estimation [2][3][4][5][6], and detection of natural selection [7][8][9][10][11][12][13]. Recently, there has been much interest in utilizing time series genetic data-e.g., from ancient DNA [14][15][16][17][18][19][20][21], experimental evolution of a population under controlled laboratory environments [22][23][24][25][26], or direct measurements in fast evolving populations [27]-to enhance our ability to probe into evolution. In particular, understanding the genetic basis of adaptation to changes in the environment can be significantly facilitated by such temporal data.…”
Section: Introductionmentioning
confidence: 99%